The efficacy of 5 rehabilitation treatments after anterior cruciate ligament reconstruction: A network meta-analysis. Issue 45 (12th November 2021) - Wang, Congxiao; Ji, Zhonglei; Wang, Luyi; Zhang, Qiaorong; Wang, Hujun; Qie, Shuyan
Abstract: Background: The efficacy of traditional rehabilitation, proprioceptive training, and neuromuscular training after anterior cruciate ligament (ACL) reconstruction is also controversial. In order to help medical staff better choose the rehabilitation treatment plan after ACL reconstruction, we conducted this network meta-analysis. Methods: Chinese and English databases such as Wanfang, Weipu, China Zhiwang, and PubMed, Cochrane Library, Embase were retrieved. We collected clinical controlled trial papers on traditional rehabilitation therapy, proprioceptive training and neuromuscular training after ACL reconstruction for meta-analysis. Results: In this meta-analysis, 12 studies were included, including 486 patients who received rehabilitation treatment after ACL reconstruction. Based on network meta-analysis, it was found that 4 groups of direct comparison and 6 groups of indirect comparison were formed for 5 rehabilitation treatment schemes after ACL reconstruction. The curative effect of traditional rehabilitation training combined with proprioception training is better than that of traditional rehabilitation training (mean difference value of traditional rehabilitation training combined with proprioception training vs traditional rehabilitation training was 8.00, 95% confidence interval: 2.61, 13.39). The efficacy of proprioceptive training is better than that of traditional rehabilitation training (mean difference value of proprioceptive training vs traditional rehabilitation training is 11.01, 95% confidence interval: 0.62, 21.39). There was no statistical significance between the other rehabilitation trainings. According to the surface under cumulative ranking curve, the therapeutic effects of the 5 rehabilitation treatment programs after ACL reconstruction were ranked as follows: proprioceptive training (72%) > traditional rehabilitation training combined with neuromuscular training (70.8%) > traditional rehabilitation training combined with proprioception training (57.1%) > neuromuscular training (45.5%) > traditional rehabilitation training (4.6%). No publication bias was found in the funnel plot. Conclusion: Combined with the results of meta-analysis and surface under cumulative ranking efficacy sequence diagram, it can be seen that traditional rehabilitation training combined with proprioceptive training and traditional rehabilitation training combined with neuromuscular training have significant efficacy. Due to the limitations of this study, the conclusions of this network meta-analysis still need to be further confirmed by a large sample size and well-designed randomized controlled trials. Abstract : Supplemental Digital Content is available in the text